2022
DOI: 10.3390/s22197282
|View full text |Cite
|
Sign up to set email alerts
|

Digital Twin-Driven Rear Axle Assembly Torque Prediction and Online Control

Abstract: During the assembly process of the rear axle, the assembly quality and assembly efficiency decrease due to the accumulation errors of rear axle assembly torque. To deal with the problem, we proposed a rear axle assembly torque online control method based on digital twin. First, the gray wolf-based optimization variational modal decomposition and long short-term memory network (GWO-VMD-LSTM) algorithm was raised to predict the assembly torque of the rear axle, which solves the shortcomings of unpredictable non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…In 2022, research on digital twin-driven rear axle assembly torque prediction and online control showed significant improvements in assembly quality and efficiency. This study is particularly relevant for the advancement of intelligent production lines, showcasing how digital twin technology can be effectively utilized for precision and control in assembly processes (Liu et al, 2022). According to Assad et al(2021) demonstrated the application of a Web-based Digital Twin (WDT) architecture to improve sustainability in assembly lines.…”
Section: Digital Shadowboardmentioning
confidence: 99%
“…In 2022, research on digital twin-driven rear axle assembly torque prediction and online control showed significant improvements in assembly quality and efficiency. This study is particularly relevant for the advancement of intelligent production lines, showcasing how digital twin technology can be effectively utilized for precision and control in assembly processes (Liu et al, 2022). According to Assad et al(2021) demonstrated the application of a Web-based Digital Twin (WDT) architecture to improve sustainability in assembly lines.…”
Section: Digital Shadowboardmentioning
confidence: 99%
“…Digital twin is regarded as the best technology to achieve the integration of the physical world and digital space, which possesses the characteristics of virtual-real mapping, data-driven, and so on. [17] By digital twin, maintenance personnel can quickly pinpoint the location of device failures without the necessity of on-site physical inspections, thereby improving maintenance efficiency. Combining TENG and digital twin, Jin et al built a soft-robotic gripper system, which displays virtual robotic manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of rear axle assembly, assembly torque is a crucial parameter to control and test the connection quality of threaded fasteners, which is the key to realize the quality control of rear axle assembly [2]. There are many factors affecting the assembly torque, such as the matching state between the screw pairs, the difference in material and hardness of the parts, the smoothness and flatness of the surface of the clamped parts, the accuracy and speed of the tightening tool and the tightening process sequence [3]. In the rear axle assembly production line, due to the vibration of the tightening gun, the wear of the fixture and the plastic deformation of the workpiece material, the output torque of the tightening gun reaches the assembly threshold, which affects the assembly quality of the rear axle.…”
Section: Introductionmentioning
confidence: 99%